1984
DOI: 10.1161/01.cir.69.5.933
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous left ventricular diastolic filling in patients with isolated disease of the left anterior descending coronary artery: assessment with radionuclide ventriculography.

Abstract: To study the relationship between global and regional filling of the left ventricle, we conducted resting gated radionuclide ventriculographic studies in 15 control subjects (group 1) and 22 patients with isolated disease of the left anterior descending coronary artery (group 2). None had had a previous myocardial infarction. A computer program subdivided the image of the left ventricle into four regions. The time-activity and first-derivative curves of the global and regional left ventricles were computed. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(38 citation statements)
references
References 32 publications
3
34
1
Order By: Relevance
“…The ischemic process impairs myocardial relaxation6' 7,[22][23][24][25][26] and results in asynchrony of left ventricular filling.7 27 When a filling pressure or a driving pressure increases, as indicated by an elevation in left ventricular end-diastolic pressure in our study, the peak rate of left ventricular filling should increase substantially. One of the factors that contributes to a blunting of the effect of an increase in a driving pressure on the left ventricular filling rate is impairment of myocardial distensibility with ischemia, which we have discussed above.…”
Section: Resultsmentioning
confidence: 73%
“…The ischemic process impairs myocardial relaxation6' 7,[22][23][24][25][26] and results in asynchrony of left ventricular filling.7 27 When a filling pressure or a driving pressure increases, as indicated by an elevation in left ventricular end-diastolic pressure in our study, the peak rate of left ventricular filling should increase substantially. One of the factors that contributes to a blunting of the effect of an increase in a driving pressure on the left ventricular filling rate is impairment of myocardial distensibility with ischemia, which we have discussed above.…”
Section: Resultsmentioning
confidence: 73%
“…[23][24][25] Earlier studies have demonstrated the presence of abnormal diastolic function in patients with CAD without evidence of systolic wall motion abnormalities by radionuclide angiography or digitized cineangiography. [26][27][28] Kondo et al have also demonstrated that delayed outward LV wall motion in the isovolumic relaxation phase by digital subtraction high-frame-rate echocardiography was indicative of CAD. 29 In our experience, a positive myocardial velocity occurring during the isovolumic relaxation phase as detected by the spectral tissue Doppler mapping technique (MOMI) was indicative of critical coronary artery stenosis in patients complaining of chest pain with visibly normal LV contraction.…”
Section: Discussionmentioning
confidence: 99%
“…11 LV nonuniformity is an important determinant of LV diastolic dysfunction because it delays LV relaxation and thus impairs diastolic filling. 4,6,7 LV asynchronies have been evaluated by left ventriculography, 7 radionuclide angiography 12,13 and echocardiography, 14 but none of these methodologies provides real-time evaluation. In this study, we have shown the diastolic asynchrony in patients with LVH using our newly developed A-SMA system, which uses an on-line system for analyzing color kinesis images, thus enabling us to quantify regional wall motion in real time.…”
Section: Discussionmentioning
confidence: 99%